The woman question - Evans, Mary 1946- (SAGE Publications, 1994)
Revised and updated edition, to reflect the transformation of women's studies over the last decade. Topics covered include contemporary feminism, the construction of the "feminine", and "femininity", and the ways in which femininity and masculinity are treated in language and the visual arts.